Initial Model of the SAHABAT Web-Based Application as an Innovation in Digital Legal Counselling for Promoting Legal Awareness - Yenny Aman Serah; Purwanto Purwanto; Febrianawati; Resmaya Agnesia Mutiara Sirait; Agustinus Astono (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
The limitations of conventional legal counselling, due to access, cost, and time constraints, create a need for more effective digital media to increase public legal awareness. The main issues examined are the need for local governments and the Regional Offices of the Ministry of Law to develop effective digital legal counseling media, and how the initial design of the SAHABAT application can be proposed as a website-based innovation to realize legal awareness. The purpose of this study is to describe institutional needs and design a preliminary model for the SAHABAT application. The method used is empirical legal research with a sociological jurisprudence approach, employing interviews and questionnaires with legal educators and village heads, and using descriptive-qualitative analysis. The results show that the SAHABAT application can provide interactive, participatory, and easily accessible legal education. The novelty of this research lies in the concrete design of the SAHABAT application as a digital legal counseling medium that reflects the theories of legal effectiveness, responsive law, and progressive law.